1984
DOI: 10.1111/j.1365-246x.1984.tb05030.x
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake prediction: a new physical basis

Abstract: Subcritical crack growth in the laboratory occurs slowly but progressively in solids subjected to low stresses at low strain rates. The cracks tend to grow parallel to the maximum compressive stress so that, when this stress is aligned over a large enough region, the cracks will also be aligned and possess effective seismic anisotropy. It is suggested that such subcritical crack growth produces extensive-dilatancy anisotropy (EDA) throughout earthquake preparation zones. This process is a possible driving mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(110 citation statements)
references
References 40 publications
5
104
0
1
Order By: Relevance
“…In industrial seismology shear-wave splitting is frequently interpreted in terms of macro-fractures enabling oil flow and aiding hydrocarbon production. Although recognising that large fractures may affect shear-wave splitting [50,51], we suggest that stress-aligned fluid-saturated microcracks are the major source of shear-wave splitting [52]. One way to distinguish crack size is by measuring and interpreting frequency-dependent seismic attenuation, where squirt flow is (probably) the dominant mechanism.…”
Section: Significance Of Pore Space In Porous Rocks: Squirt Flow Thementioning
confidence: 99%
“…In industrial seismology shear-wave splitting is frequently interpreted in terms of macro-fractures enabling oil flow and aiding hydrocarbon production. Although recognising that large fractures may affect shear-wave splitting [50,51], we suggest that stress-aligned fluid-saturated microcracks are the major source of shear-wave splitting [52]. One way to distinguish crack size is by measuring and interpreting frequency-dependent seismic attenuation, where squirt flow is (probably) the dominant mechanism.…”
Section: Significance Of Pore Space In Porous Rocks: Squirt Flow Thementioning
confidence: 99%
“…These investigations have shown that crack propagation rates are highly dependent on moisture content and stress rates and, more importantly, that subcritical fracture growth continues at stress levels that are less than 20% of those required for catastrophic failure (MEREDITH and ATKINSON, 1983;ATKINSON, 1984;FREIMAN, 1984). Recent papers by CRAMPIN et a/., (1984) and CRAMPIN (1987) have suggested that several geophysical earthquake precursors could be explained by pervasive subcritical crack growth and I would suggest that this same phenomenon could also account for many of the dissolved gas and ground gas chemical anomalies that have been observed at substantial distances from an impending earthquake. The contribution of the IRSA model to precursory changes in dissolved ion chemistry is, however, likely to be limited because of the slow reaction rate of most minerals with groundwaters.…”
Section: Increased Reactive Surface Area Modelmentioning
confidence: 99%
“…For instance, Crampin et al (1984) suggest that fluidfilled microcracks and intergranular pore spaces may be reactivated before the main shock in the earthquake preparation zone. It is generally well established that fluid-saturated regions may provide more insights for the understanding of precursors of seismic events (Rice & Rudnicki 1979;Roeloffs 1988;Sammonds et al 1992;Park et al 1993;Chadha et al 2003;Skelton et al 2014).…”
Section: Discussionmentioning
confidence: 99%